A SEMIOTICS STUDY OF CHARACTERIZATION ON THE MOVIE AND VISUAL NOVEL ADAPTATIONS OF ANDERSEN’S THUMBELINA - Fadzilah, Resita Marif; Untari, Lilik; Purnomo, SF. Luthfie Arguby (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
This research is a case study which employs qualitative method to analyze signs and symbols showed through characterization in the Thumbelina animation movie produced by Warner Bros. and Tiny and Her Necklace visual novel, SPARRING product. Both of them are adapted from Anderson’s Thumbelina. In analyzing those signs and symbols, this research applies Pickering and Hoeper characterization method, specifically method of telling and showing. It also uses Pierce’s semiotics theory of triangle meaning to elaborate the analysis. In semiotics perspective, characterization relates with the use of signs or symbols to describe the characters based on character traits. There are similarities and differences in characterization and signs presented in both movie and visual novel. The similarity is the novel and visual novel designate and symbolize the main character, Thumbelina, as a girl who is powerless and innocent. Meanwhile the man character is described as strong and brave character. The differences of both the adaptation works are concerning with the plot of the story, characterization and sign or symbol presented, and moral value delivered to the audience. The movie is adapted faithfully and the visual novel is adapted loosely from the original short story. The movie tends to use showing method. On the other hand, the visual novel is likely to use telling method. DOWNLOAD ABSTRACT